Rigidity and fuzziness within the framework of English Statutes and Law Reports. Original French title: Rigidité et Fluidité dans les cadres Législatif et jurisprudentiel anglais - Wagner, Anne (International Journal of Speech, Language and the Law, 2001)
The thesis uses a substantial corpus which spans a period of 100 years to examine English legal discourse and the appropriateness of law as a specialized language and as a linguistic medium. The analysis has three main foci: (1) the analysis of the message content by means of refining the techniques of semioticians and linguists, (2) the study of English history and its influence on the language of English law and (3) the technical and specialized contributions of jurists and judges (from the civil, the administrative or the criminal register). Two layers within the discourse are then distinguished in this study: rigidity and fluidity which show a permanency and renewal. A major concentration in the study is vocabulary relations. Legal words have a peculiar tenacity – an ability to achieve stability within changing social and economic conditions (Gény 1922) although the illusion is of conservatism, rigidity and uniformity – because the social structure penetrates into the architecture of legal language. That is why every past and present society has its own knowledge of words, and many have created new words or modified the meanings of existing words in order to reflect their particular standards and expectations (Hobbes 1971), as shown below for the word ‘night’: Under the Night Poaching Act 1828, s.12, it is stated that “the night shall be considered and is hereby declared to commence at the expiration of the first hour of sunset, and to conclude at the beginning of the last hour before sunrise”. Under the Customs and Excise Management Act 1979, s.1 “night means the period between 11 p.m. and 5 a.m.”. Under the Highways Act 1980, s.329(1) it “means the time between half an hour after sunset and half an hour before sunrise”. Moreover, this web-like semantic organization – described by Eco (1976) as a multi-levelled maze – demonstrates complexity which arises from the specific activities of professionals (either judges, jurists or MPs) who impose their definitions and contributions upon historical, economic and social events showing, for example, a conflict with the contemporary grammar: In any Act, unless the contrary intention appears, (a) words importing the masculine gender include the feminine; (b) words importing the feminine gender include the masculine; (c) words in the singular include the plural and words in the plural include the singular. (Interpretation Act 1978, s.6) Therefore, it is highly important to show how lexical items, created or modified by jurists, judges and MPs, slot into the common language and how the factual references turn the semantic content into a technical language: history, aspects of generalization (‘dis-individual’ in Delmas-Marty 1986: 25), judicial actors and formal systems have an influence over the meanings of legal terms. One more obvious and important point emerges; that text-organizing vocabulary (Coltier and Turco 1988) functions on the surface of some specific genre discourses (Kevelson 1988, 1991). Three genre discourses are examined: prescriptive, descriptive and explanatory registers. Their analysis demonstrates that the influence of judicial speech is, paradoxically, a source of both rigidity and fuzziness. Besides, this language of the law has developed in a social context, meaning that it will gradually change according to the social and historical circumstances of the country (Carbonnier 1978). Thus another genre factor to be reckoned with is related to the difference between academic science and popular science, i.e. professionals of the field and lay people. Indeed words have their own legal tradition (history) or silent backgrounds (specialized meanings) which can only be understood by a professional of the field. Given this criterion, lay individuals are in a state of perplexity because the language of the law has developed without taking into account everybody’s personal background (‘a language of fool’ in Gridel 1994). And so, there is a clear division between non-practising people and practitioners as shown below with the word complainant: one who makes a complaint to the justices (Jowitt Dictionary) In subsection (1) of this section “complainant” means a woman upon whom, in a charge for a rape offence to which the trial in question relates, it is alleged that rape was committed, attempted or proposed (Sexual Offences (Amendment) Act 1976, s.3) Moreover, English law still interlocks with other European Union member countries’ legal architectures and will affect their future evolution. So, the last issue highlighted in this thesis – ‘LSP translation’ – considers that words do not develop along the same path in all languages. Indeed, as languages are influenced by the culture and the history they are part of (the fuzzy part), LSP translators must find acceptable words in the other language in order to produce an acceptable translation. As a result they must avoid mismatches between the source-language (Legal English) and the target language (Legal French). That is the reason why the primary task for translation consists in exploring the common territory where legal English terms and legal French words can work together and share the knowledge that belong to both (the rigid part). The main aim of LSP translation will then be to develop the ability of translators to perfectly comprehend both English and French legal reasoning, the nature of the subject, and the subject treated, so that translators may express themselves as justly as if they wrote the original. REFERENCES Austin, J. L. (1970) Quand dire, c’est faire, Paris: Editions du Seuil. Carbonnier, J. (1978) Sociologie juridique, Paris: P.U.F. Coltier, D. and Turco, G. (1988) ‘Des agents doubles de l’organisation textuelle: les marqueurs d’intégration linéaire’, Pratiques, 57: 40–60. Delmas-Marty, M. (1986) Le flou du droit, Paris: P.U.F. Eco, U. (1976) A Theory of Semiotics, Bloomington: Indiana University Press. Gény, F. (1922) Science et Technique en Droit Privé Positif, Tome 1, Paris: Recueil Sirey. Goodrich, P. (1990) Languages of Law (from Logics of Memory to Nomadic Masks), London: Weidenfeld & Nicolson. Gridel, J.P. (1994) Introduction au droit et au droit français, Paris: Dalloz. Halliday, M.A.K. (1978) Language As Social Semiotics, London: Edward Arnold. Hobbes, T. (1971) Léviathan, Paris: Tricaud Kevelson, R. (1988) Law as a System of Signs, London: Plenum. Kevelson, R. (1991) Action and Agency, New York: Peter Lang. Lerat, P. (1995) Les langues spécialisées, Paris: P.U.F.